Veículos elétricos e a geração distribuída a partir de sistemas fotovoltaicos - Silva, Jardel Eugenio da (2019)
The electric vehicle (VE) is not a recent technology, in the passage from the nineteenth century to the twentieth most cars were electric, this was due to their reliability and cleanliness if compared to those driven by internal combustion engine, but with the evolution and reduction of the price of internal combustion engines, the electric vehicles were forgotten, and almost a century later they returned due to the significant increase in the price of fossil fuels as well as the concern for the environment. This study addresses the current existing technologies, which classify electric vehicles (VEs), Pure, hybrid, plug-in hybrid, plug-in to grid, the steps of converting a conventional vehicle to 100% electric, and finally, the grid-connected Photovoltaic System (SFVCR) design and its interaction with the electric vehicle. With increasing accessibility and increasing demand for motor vehicles powered by thermal fuels, and the characteristic pollution of this type of motor, electric vehicles appear as a less polluting alternative and is increasingly being shown as a solution to the high prices of fuels used in vehicles with an internal combustion engine (MCI), in addition to having a number of advantages over MCI vehicles, as they are simpler and require less use and replacement of parts, reducing maintenance costs, and not emitting pollutants to the environment, but one of the major issues of electric vehicles is their high cost of acquisition, making them inaccessible to a large part of the population, on the other hand, the conversion of conventional to electric vehicles has proven to be a viable alternative. With the objective of verifying if it is possible to convert a conventional vehicle to electric at a reasonable cost, and that performs well with a good kWh per km ratio, the conventional vehicle of the Mercedes Benz model A 190 was converted to 100% electric, and after several tests the results proved to be viable, since it reached an average of 22 cents per kilometer at a cost of 76 cents per kWh, which could reach zero with the use of solar radiation to generate electricity, through photovoltaic panels, and configure it as an environmentally sustainable solution. One of the great questions for urban centers in this means of transport is how to supply the energy demand of this new charge in the electric system. This study correlated the electric power generation data of grid-connected photovoltaic systems (SFVCR), and it was possible that the electric energy generated from these systems, supposes the demand of charging the batteries of the vehicles electrical, and is a promising form of electric power generation in urban centers. Finally, the photovoltaic generation of the UTFPR Carport proved to be a sustainable, clean and efficient form of distributed generation of electric power, being able to meet the needs of charging the batteries of the Eco Auto for average daily routes of 60 km.